Propiedades psicométricas de la escala de ansiedad ante la muerte de Templer en sujetos mexicanos (2010)
This research adapted Templer's Death Anxiety Scale (1970) for Mexican Spanish and obtained psychometric properties for two samples of Mexican adults. A total of 314 subjects were interviewed, 165 of whom were elderly adults (97 women, average age 61.7, SD = 9.7 and 68 men, average age 62.7, SD = 8.3) and 149 undergraduate students (132 women, average age 19.4, SD = 1.3 and 17 men, average age 19.9, SD = 1.3. The scale was changed to a four point Likert scale. The principal component analysis with varimax rotation, applied to the data from both samples (elderly adults and undergraduate students), yielded 3 factors for each group. The factor structure obtained from the responses provided by the undergraduate students only slightly agreed with that reported by Tomás-Sábado and Gómez-Benito (2002) for an equivalent Spanish sample. Internal consistence for elderly adults was a=.86, and a=.83 for undergraduate students. Discriminant validity was documented. The version of Templer's Death Anxiety Scale presented would seem to have adequate psychometric properties for its use with elderly Mexican adults. Finally, the results provide evidence of the possible impact the cultural differences between Spanish-speaking nations and generations have on the psychometric properties of the scale.